(untitled) (Research, Society and Development, 2022)
The research aims to evaluate the effectiveness of neuraxial anesthesia compared to general anesthesia for procedures in the lower half of the body. This is an integrative literature review carried out through the Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature on Health Sciences (LILACS) and Medical Literature Analysis and Retrieval System Online (MEDLINE) databases. of the following Health Sciences Descriptors (DeCS): “General Anesthesia” and “Caudal Anesthesia”. Combined with each other by the AND operator. As inclusion criteria: articles available in full, in Portuguese, English and Spanish, that addressed the topic, in the last five years (2017-2022). As exclusion criteria: articles that did not contemplate the theme and studies repeated in the databases. From the initial search with the descriptors and Boolean operator defined, 90 studies were found in the selected bases and after applying the inclusion criteria, 7 studies were selected to compose the final sample. Given the above, we can see that neuraxial block is superior to general anesthesia in view of greater cost benefit, less associated complications.